Railway slab vs ballasted track: A comparison of track geometry degradation. (16th May 2023) - Charoenwong, C.; Connolly, D.P.; Colaço, A.; Alves Costa, P.; Woodward, P.K.; Romero, A.; Galvín, P.
Highlights: A novel numerical model is presented compute track geometry deterioration. Train-induced differential settlement for ballast and non-ballasted tracks is investigated. Differential settlement of track structures is studied for varying train speeds. Ballasted tracks exhibits higher train-induced differential settlement compared to slab. At higher train speeds, slab track shows enhanced performance. Abstract: Concrete slab railway tracks typically have higher initial capital costs yet lower operational costs in comparison to ballasted tracks. One reason for the elevated operational costs on ballasted lines is the need for more frequent maintenance (e.g. tamping to maintain track geometry). Therefore on higher linespeed routes where maintenance windows are limited, concrete slab track is a common choice of trackform. In contrast, on lower linespeed routes it's common to opt for ballasted track structures. However, the speed ranges at which the two different trackforms are most suitable has received limited scientific analysis. Therefore this paper aims to investigate the train-induced differential settlement of ballast and non-ballasted tracks, considering typical modern intercity (200 km/h) and high speed (300 km/h) lines. Vertical railway track geometry is the metric used to analyse maintenance requirements. This is because it defines the longitudinal level of railway tracks and is a common metric used for the scheduling of track maintenance. First a novel numerical model is presented capable of computing track geometry deterioration due to repeated load passages. The model is then validated for both ballast and concrete slab tracks. Finally it is used to study the differential settlement of both track structures at the two train speeds. It is shown that the ballasted track exhibits higher train-induced differential settlement compared to the slab and at higher linespeeds the degradation of track geometry is increasingly pronounced for the ballasted track.